1992
DOI: 10.1159/000129200
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for the Existence of Preformed Antibodies against Hydroxyethyl Starch in Man

Abstract: Using the highly sensitive ELISA technique for detecting anti-hydroxyethyl starch (HES) antibodies in man sera from 1,056 patients were analyzed. Patients of both sex, who had never had any prior contact with HES, were included in the study. In none of the cases could any titer of HES-reactive antibodies be detected. These data suggest that in man preformed HES-reactive antibodies do not exist or are extremely rare. In any case, unlike dextran-reactive antibodies, they should not have a high clinical importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…21, 33-36 The HES method for blood volume estimation is a rapid, safe, and acceptable technique for use in pregnant patients, and does not cross the placenta. 32,33,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…21, 33-36 The HES method for blood volume estimation is a rapid, safe, and acceptable technique for use in pregnant patients, and does not cross the placenta. 32,33,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…In addition to dextran, HES is also used as a colloid solution for volume expansion. Although there are several case reports on HES-induced anaphylactic reactions [ 16 19 ], the incidence of such reactions to HES is extremely low compared with dextran [ 9 , 20 , 21 ]. While DRAs are found in most adults, HES-reactive antibodies are extremely rare [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…HES is a synthetic polymer derived from amylopectin, a waxy starch of maze. The reason for the low incidence of antibodies to HES is that the structure of HES resembles that of glycogen [ 20 , 21 ]. Although HES may induce dilution of coagulation factors, HES can be administered instead of dextran in cases where tight hemostasis is completed during operation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,13,15,22,23 Using an enzyme-linked immunosorbent assay, Kraft et al 24 demonstrated absence of anti-HES antibodies in sera from 1,056 patients, concluding that preformed HES-reactive antibodies either do not exist in humans or are extremely rare. Dieterich et al…”
Section: Discussionmentioning
confidence: 99%